2013
DOI: 10.1116/1.4802928
|View full text |Cite
|
Sign up to set email alerts
|

Poly-(3)hexylthiophene nanowire networks for versatile fabrication of bulk heterojunctions with increased active volume

Abstract: Spontaneous demixing of poly-(3)hexylthiophene (P3HT) and polystyrene (PS) generates a dense array of crystalline P3HT nanowires embedded in a PS matrix. The PS phase is subsequently removed, to form a network of P3HT nanowires with a greatly enhanced surface area-to-volume ratio relative to a planar P3HT film. Photovoltaic devices fabricated from these networks backfilled with either organic ([6,6]-phenyl-C 61-butyric acid methyl ester (PCBM)) or inorganic (cadmium selenide (CdSe) nanocrystals) material have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…The surface roughness values for the amorphous 20-and 40-monomer films are 2.56 Å and 4.83 Å, respectively. Experimentally measured contact angle values are in the range of 102 • to 109 • , [18,19,20,21] in good agreement with our simulation results (backbone-exposed and amorphous films). The variation in the experimentally measured contact angles is due to differences in surface morphology as a result of different film processing conditions.…”
Section: Contact Anglesupporting
confidence: 89%
See 1 more Smart Citation
“…The surface roughness values for the amorphous 20-and 40-monomer films are 2.56 Å and 4.83 Å, respectively. Experimentally measured contact angle values are in the range of 102 • to 109 • , [18,19,20,21] in good agreement with our simulation results (backbone-exposed and amorphous films). The variation in the experimentally measured contact angles is due to differences in surface morphology as a result of different film processing conditions.…”
Section: Contact Anglesupporting
confidence: 89%
“…The calculated contact angles are in agreement with experimentally measured values. [18,19,20,21] Though large differences in surface tension values (P3HT/vacuum) and contact angle values were observed between hexyl-and backbone-exposed films, their interfacial surface tension with water was found to be comparable. The water molecules' orientations on hexyl-exposed and amorphous films were similar because hexyl side chains enriched both surfaces.…”
Section: Discussionmentioning
confidence: 73%
“…The PS in the liquid state is then solidified by producing P3HT nanowires embedded in the PS matrix. This structure is extremely efficient for maintaining percolation of the channel at low P3HT content [52][53][54][55][56]. In addition, environmental stability of OFETs was enhanced greatly, as the PS matrix protects H 2 O and O 2 molecules from ambient air.…”
Section: Embedded Semiconductor Nanowiresmentioning
confidence: 90%
“…In the literature, there are two approaches to the formation of P3HT-nw. Several studies report that nanowire formation direction is toward to π-π stacking direction [20][21][22][23][24]. On the other hand, in a previous study, we reported that the polymer backbones are parallel to the nanowire axis [17].…”
Section: Introductionmentioning
confidence: 65%